Micelles, Membranes, Microemulsions, and Monolayers - Gelbart, William M.; Ben-Shaul, Avinoam; Roux, Didier; SpringerLink (Online service) (New York, NY : Springer New York, 1994)
Over the last decades, the study of surfactants (detergents, for example) has been profoundly changed by ideas and techniques from physics, chemistry, and materials science. Among these are: self assembly; critical phenomena, scaling, and renormalization; high-resolution scattering, and magnetic resonance spectroscopy. This book represents the first systematic account of these new developments, providing both a general introduction to the subject as well as a review of recent developments. The book will be a very useful tool for the biophysist, biochemist or physical chemist working in the field of surfactants.
1 Statistical Thermodynamics of Amphiphile Self-Assembly: Structure and Phase Transitions in Micellar Solutions -- 1.1 Introduction -- 1.2 Amphiphile Self-Assembly in Dilute Solutions -- 1.3 Molecular Organization of Aggregates -- 1.4 Interaction Effects in Dilute Solution and Beyond -- 1.5 Concluding Discussion -- 2 Micellar Growth, Flexibility and Polymorphism in Dilute Solutions -- 2.1 Introduction -- 2.2 Globule to Rod Transformation -- 2.3 Polymerlike Behavior -- 2.4 Bidimensional Aggregation -- 2.5 The Physical Basis of Micellar Polymorphism -- 2.6 Connection with Microemulsions -- 3 Micellar Liquid Crystals -- 3.1 Introduction -- 3.2 Nomenclature -- 3.3 Preparation of Stable Nematic Phases -- 3.4 Factors Governing Size and Shape of Micelles in Concentrated Solutions -- 3.5 Experimental Characterization of Nematic Phases -- 3.6 Phase Transitions in Micellar Solutions -- 3.7 Conclusions -- 4 Geometrical Foundation of Mesomorphic Polymorphism -- 4.1 Introduction -- 4.2 Mesophases as Structures of Films -- 4.3 Frustration, Curved Spaces and Disclinations -- 4.4 The Periodic System of Parallel Films -- 4.5 Comments -- 4.6 Conclusion -- 4.7 Appendix -- 5 Contents Lamellar Phases: Effect of Fluctuations (Theory) -- 5.1 Introduction -- 5.2 Model of Isolated Membranes -- 5.3 Membranes in Interaction -- 5.4 Conclusion -- 5.5 Appendix -- 6 Lyotropic Lamellar L? Phases -- 6.1 Introduction -- 6.2 Phase Diagrams -- 6.3 Membranes and Smectic Properties -- 6.4 Static Scattering Studies of Lyotropic Lamellar Phases.. -- 6.5 Dynamic Light Scattering -- 6.6 Conclusion -- 7 The Structure of Microemulsions: Experiments -- 7.1 Introduction -- 7.2 The Interfacial Film of Surfactant -- 7.3 Dilute Microemulsions -- 7.4 Structure of Concentrated Microemulsions -- 7.5 Conclusions -- 7.6 Appendix: X-ray and Neutron Scattering -- 8 Lattice Theories of Microemulsions -- 8.1 Introduction: Aims of a Lattice Theory of Microemulsions -- 8.2 The Lattice Formulation -- 8.3 Some Results of the Three Component Model -- 8.4 Some Results of Other Lattice Models -- 8.5 Comparison with Phenomenological Models -- 9 Fluctuating Interfaces and the Structure of Microemulsions -- 9.1 Introduction -- 9.2 Experimental Observations and Theoretical Models -- 9.3 Fluctuation of Microemulsions -- 9.4 Lamellar and Random/Bicontinuous Systems -- 9.5 Outstanding Problems -- 10 Interfacial Tension: Theory and Experiment -- 10.1 Introduction -- 10.2 Experimental Techniques and Data Analysis -- 10.3 The Bending Elasticity of Monolayers: Experimental Results -- 10.4 Experimental Study of Low Surface Tensions in Winsor Equilibrium -- 10.5 Structure of the Oil Microemulsion and the Water Microemulsion Interfaces in Winsor Equilibria -- 11 Critical Behavior of Surfactant Solutions -- 11.1 Introduction -- 11.2 Structure and Interactions -- 11.3 Critical Phenomena -- 11.4 Conclusion -- 12 Structures and Phase Transitions in Langmuir Monolayers -- 12.1 Introduction -- 12.2 The Experimental Situation -- 12.3 Equilibrium Theories of Monolayers -- 12.4 Dynamical Properties of Amphiphilic Monolayers -- 12.5 Conclusions and Future Prospects.
Keywords: Physics; Chemistry, Physical organic; Biochemistry; Surfaces (Physics).; Physics; Biophysics and Biological Physics; Biochemistry, general; Physical Chemistry; Surfaces and Interfaces, Thin Films